Pengajaran bahasa asing dengan pendekatan budaya: Menggali motivasi dan efektivitas pembelajaran - Noverita, Zalsabilla Laily (Maliki Interdisciplinary Journal, 2024)
The teaching of foreign languages has undergone significant evolution in recent decades. One approach that has been garnering increasing attention is language instruction that incorporates cultural elements. This research aims to explore the potential for motivation and the effectiveness of learning within the context of teaching foreign languages using a cultural approach. This approach integrates cultural aspects of the target language into the learning process, aiming not only to teach grammar and vocabulary but also to understand the cultural concepts that underlie the language. In this study, we adopted a mixed-methods approach involving surveys with a group of students participating in a language learning program with a cultural approach, as well as in-depth interviews with several language instructors. The research findings indicate that teaching foreign languages with a cultural approach has a positive impact on student learning motivation. Cultural elements provide relevance and deeper meaning for students, encouraging them to engage actively in their learning. Students reported higher levels of satisfaction with this form of instruction, as they felt more connected to the culture associated with the language they were studying. Furthermore, this study also evaluated the effectiveness of teaching foreign languages with a cultural approach in achieving language learning objectives, such as mastering grammar rules and speaking skills. The findings suggest that learning focused on cultural contexts can assist students in more easily internalizing language structures and applying them in real communicative situations. However, challenges such as a packed curriculum and resource limitations were also identified in implementing this approach. Therefore, this research presents recommendations for developing curricula and teaching strategies that can more effectively harness the potential of the cultural approach in foreign language education. In conclusion, teaching foreign languages with a cultural approach holds significant potential for enhancing motivation and learning effectiveness. The integration of culture into language instruction not only creates a more engaging and meaningful learning environment but also aids students in gaining a deeper understanding of the cultural context underlying the language they are studying.